Evolution of behavioural resistance in host–pathogen systems - Amoroso, Caroline R. (Biol Lett, 2020)
Behavioural resistance to parasites is widespread in animals, yet little is known about the evolutionary dynamics that have shaped these strategies. We show that theory developed for the evolution of physiological parasite resistance can only be applied to behavioural resistance under limited circumstances. We find that accounting explicitly for the behavioural processes, including the detectability of infected individuals, leads to novel dynamics that are strongly dependent on the nature of the costs and benefits of social interactions. As with physiological resistance, evolutionary dynamics of behavioural resistance can also lead to mixed strategies that balance these costs and benefits.